The Tergal Gland Secretion of the Two Rare Myrmecophilous Species Zyras collaris and Z. haworthi (Coleoptera: Staphylinidae) and the Effect on Lasius fuliginosus. (31st March 2013) - Stoeffler, Michael; Boettinger, Lea; Tolasch, Till; Steidle, Johannes L. M.
Abstract : The beetle species Zyras collaris and Z. haworthi belong to the rove beetle tribe Myrmedoniini (Staphylinidae: Aleocharinae), which comprises many myrmecophilous species. Due to their rareness, it is unknown how the two species interact with their host ants. GC-MS analyses revealed that both species release α -pinene, β -pinene, myrcene and limonene from their defensive tergal glands. This composition of tergal gland secretion is unique within the subfamily Aleocharinae. In biotests, Lasius fuliginosus ants showed increased antennation towards filter paper balls treated with mixtures of these substances in natural concentrations. Because these monoterpenes are also present in some aphid species which are attended by ants, we hypothesize that Zyras beetles mimic the presence of aphids and thereby achieve acceptance by their host ants.